The Effect of Contextual Digital Teaching Materials and Creativity on Students’ Scientific Literacy in the Digital Era - Yanti Nainggolan, Irma; Hasibuan, Lily Rohanita; Harahap, Amin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
Students’ scientific literacy remains low due to the continued use of conventional learning methods that are less contextual and interactive. This study aims to determine the effect of context-based and creative digital teaching materials on students’ scientific literacy. A quasi-experimental pretest-posttest control group design was used involving 60 seventh-grade students divided into an experimental class (n = 30) and a control class (n = 30). The instruments included scientific literacy tests, questionnaires, and observation sheets. The results showed that the average posttest score of the experimental class (30.03) was significantly higher than that of the control class (24.50), with t(58) = 2.38, p = 0.021. The N-Gain value of the experimental class was 0.21 (low category), which was higher than the control class at 0.004 (low category). These findings indicate that context-based and creative digital teaching materials are effective in improving students’ scientific literacy, although the level of improvement remains low.